Productive parameters of growing lambs fed an extruded ration with different roughage: concentrate ratios - Oliveira, Karla Alves (2019)
Feed consumption has a great influence on the growth and performance of animals since the intake of dry matter supplies the quantity of nutrients that are necessary to meet the maintenance and production requirements of these animals. The objective of this study was to evaluate the dry matter intake, body growth, weight gain and carcass characteristics (by ultrasonography) of lambs fed an extruded ration at different roughage (R): concentrate (C) ratios. Thirty mixed race (Santa Inês x Dorper) lambs, aged 3 months and with an average weight of 20 kg, were used. The treatments consisted of an extruded ration in 30R:70C and 70R:30C ratios, completely randomised to 2 treatments and 15 replicates. The means of the variables were evaluated using a Tukey test and a regression at the 5% significance level. Dry matter intake (DMI), weight gain, body growth, evaluated through biometric measurements, and carcass characteristics, evaluated by ultrasonography, were assessed. There was a reduction of DMI in relation to body weight during the experimental period, with lower DMI amongst the animals in the 30R:70C treatment. There was a quadratic effect for the growth variables hindlimb height, forelimb height, body length, thoracic and barrel circumference over time, indicating that the animals presented adequate body growth, with intense development during the experimental period and stabilisation at the end of the experiment. There was no difference in the animals' weight gain, with an average daily gain of 182.79 g day-1. There was a difference in carcass characteristics throughout the evaluation period, with a larger loin eye area, body condition score and subcutaneous fat thickness at the end of the experimental period. The use of an extruded ration with a 30% roughage and 70% concentrate ratio promotes better feed efficiency in lambs, since it achieved the same weight gain and body development with lower dry matter intake.